Penerapan Algoritma Fuzzy C-Means untuk Melihat Pola Penerima Beasiswa Bank Indonesia - Agung Surya Maulana; Alwis Nazir; Lestari Handayani; Iis Afrianty (STMIK Budi Darma, 2023)
Scholarship is a program in the form of financial assistance aimed at individuals to continue their education with the aim of helping reduce the financial burden during the study period, especially in difficult situations, so that it can help expedite the learning process. Based on data related to scholarship recipients obtained in 2020, 2021 and 2022, analysis is needed to see the characteristics of Bank Indonesia scholarship recipients because Bank Indonesia does not yet know this, this was said directly by the Bank Indonesia Scholarship supervisor. The method needed for grouping data is data mining with the Fuzzy C-Means algorithm and using a computerized system, namely the RapidMiner application. This study uses the Cumulative Grade Point Average (GPA), Semester, and Study Program variables. The research results obtained were at Riau University for three years, the pattern formed was students of the Faculty of Social and Political Sciences with a large GPA of 3.5. At Sultan Syarif Kasim Riau State University, Riau Muhammadiyah University, and Lancang Kuning University have the same pattern, namely students with a GPA above 3.5. Then at the Dumai College of Technology, namely Informatics Engineering students with a large GPA of 3.5